Seabed Protection Systems to prevent Scour from High-Speed Ships - Evans, G. (Department of Engineering Systems and Management, 2010)
This document reviews the scour protection systems required around port structures where these are to be used for the berthing of vessels powered by water jet systems. The development of a scour protection system at Poole Harbour in Dorset has been documented and reviewed and a series of laboratory investigations were then undertaken. This has enabled a greater understanding of the scour mechanisms from the water jet propulsion systems of High Speed Ships. This work has shown that current design guidance on scour protection is not appropriate for use on berths used by High Speed Ships, that failure of these systems can occur rapidly and catastrophically, and secondary effects from water jets may promote the failure of quay walls. The scour protection system should comprise two individual elements, a filter layer and an armour layer. It has been found that systems involving individual isolated armour units are inappropriate and prone to failure and that shaped linked armour blocks need to be used. The loads on the armour layer were also found to be oscillatory and the materials used for both the armour and filter layers need to be designed for cyclic fatigue loading and fretting. Water jets are also capable of reducing the strength of permeable, seabed strata.